Analisis Perbandingan Kinerja Sinkronisasi OFDM Antara Metode Konvensional dengan Statistik Korelator Simetris - Shelvi Eka Tassia (CV. Multi Kreasi Media, 2022)
OFDM is a technology that can be used in various long-distance communication systems that are currently being developed, both on LAN, WLAN, 3G, or 4G, even 5G. One of the problems faced by OFDM technology is the weakness of the OFDM system itself, namely sensitivity to carrier frequency offset (CFO) and the difficulty of signal synchronization in OFDM. This study aims to analyze several comparisons between the conventional OFDM synchronization method used here and symbol training, then compared with the symmetric correlator statistical method. From the research results, the mean square error (MSE) is quite good, which ranges from 9.3 x 10-3 at an input SNR of 0 dB and at an input SNR of 30 dB with an MSE of 1.68 x 10-5. Where the greater the Signal to Noise Ratio, the smaller the value of the mean square error (MSE). The position of the symmetrical correlator used also affects the results of the synchronization performed. Synchronization accuracy will be maximized when using the maximum correlator.